Comparison of Pregabalin and Sodium valproate in Pediatric Migraine Prophylaxis: A Randomized Clinical Trial: Comparing Pregabalin and Sodium Valproate in Pediatric Migraine Prophylaxis: A Randomized Clinical Trial - Jafari, Narjes; Nasiri Eghbali, Aiden; Taghdiri, Mohammad Mahdi; Karimzadeh, Parvaneh (Iranian Journal of Child Neurology, 2023)
Objectives: Migraine is a common disorder in children that its prophylaxis with minimal side effects is momentous. This study aimed to compare the efficacy of Pregabalin and Sodium valproate in preventing migraine attacks. Material & methods: Sixty-four children (aged 6-18) with migraines were recruited, as defined by Internation Headache Criteria (ICHD-III). They were randomly assigned to two groups: Sodium Valproate (n=32) and Pregabalin (n=32). The minimum dosage of drugs was prescribed in both groups. The patients were followed for four months. The parameters such as frequency, intensity, duration of migraine attacks, and the number of painkillers that the patients used monthly were recorded. The Spence Children’s anxiety scale was also used to evaluate medications’ effect on patients’ anxiety levels. Results Two medications were equally effective in reducing the intensity and duration of attacks. Additionally, their effect on reducing the anxiety level of patients was equal. There was a significant difference between the effect of drugs on the frequency of migraine attacks at the end of the first and fourth months and the number of painkillers used at the end of the fourth month. The frequency of attacks was decreased by more than 50% in twenty-eight patients (90%) of Pregabalin recipients and twenty-one patients (84%) of Sodium Valproate recipients. Conclusion considering the better effect of Pregabalin in the reduction of frequency of migraine attacks and pain-reducing medications consumption, Pregabalin could be a proper substitute to Sodium valproate for migraine prophylactic treatment in children.